Estudio de factibilidad para la creación de una empresa productora y comercializadora de bocadillo a base de frutas orgánicas con propiedades fitoterapeuticas en la ciudad de Bogotá, D.C. (2019)
The present study has been made begging with a diagnosis of the main variables that influence in the economic development of the country, the industry and the sector; in order to determine if there are favorable conditions to the companies in Colombia. Later it developed the market research that helps to determine the segment of the project resulting people between 20 and 59 years that belong to the strata 4, 5 and 6 and live in Suba; that define the main characteristics of the target customer also it has been made an analysis of demand and offer of the product.